Habitat Space Used by Northern Bobwhites and Texas Tortoises on South Texas Rangelands - Ross O. Couvillon; Leonard A. Brennan; Fidel Hernández; Bart M. Ballard; Thomas V. Dailey (National Quail Symposium Proceedings, 2017)
South Texas rangelands are increasingly managed for recreational hunting, particularly northern bobwhite (Colinus virgianus). Effects of habitat management for game species on non-game species are largely unknown. Large private ranches used for recreational hunting could also provide habitat for the threatened Texas tortoise (Gopherus berlandieri). We studied habitat use of Texas tortoises and northern bobwhites on a private ranch in South Texas that undergoes active habitat management. In 2015, tortoises (n = 12) and bobwhite hens (n = 42) were tracked during their active and breeding seasons, respectively, with radio-telemetry. Satellite images were analyzed using ArcGIS 10.3 to delineate habitat through unsupervised classification for relevant habitat categories. Habitats were delineated based on reflectance. Differences in percent habitat composition of observed and random home ranges (100% Minimum Convex Polygon) of tortoises were not significant, but were significant for quail in 3 of 5 habitat categories in only 1 of 2 pastures. These observed quail home ranges included more areas corresponding to light woody cover and moderate herbaceous cover and fewer areas corresponding to sparsely vegetated or bare ground than random home ranges. Tortoise home ranges included more areas with woody brush cover than bobwhite home ranges. Bobwhite home ranges included more areas associated with moderate grass and herbaceous cover than tortoises. This study will continue in 2016 and will include more quail home ranges in areas with tortoises. This research seeks to determine the compatibility of managing for recreational hunting while maintaining landscape characteristics important to Texas tortoises.
Keywords: northern bobwhite; colinus virginianus; texas tortoise; gopherus berlandieri; habitat compatibility; habitat use; non-game; sympatry